Developing Reflective Practice through Reflective Actions - Yanuarti, Endah (Curtin University, 2017)
The objective of this research was to understand Indonesian teachers’ applications of reflection in their daily practice by examining their reflective conversations, writing and videos in relation to the Teacher Competency Standards. This qualitative case study included two phases which revealed that teachers’ limited understanding of reflection was mostly on how to prepare, deliver and evaluate lessons. The study identified and developed a model of reflective practice to improve Indonesian teachers’ teaching practice.